2021
DOI: 10.1007/s43440-021-00274-8
|View full text |Cite
|
Sign up to set email alerts
|

Insights into a possible role of glucagon-like peptide-1 receptor agonists in the treatment of depression

Abstract: Depression is a highly prevalent mood disorder and one of the major health concerns in modern society. Moreover, it is characterized by a high prevalence of coexistence with many other diseases including metabolic disorders such as type 2 diabetes mellitus (T2DM) and obesity. Currently used antidepressant drugs, which mostly target brain monoaminergic neurotransmission, have limited clinical efficacy. Although the etiology of depression has not been fully elucidated, current scientific data emphasize the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 125 publications
0
28
0
Order By: Relevance
“…In the hippocampus, in addition to a decrease in the level of SNAP-25 in the model of depression and the coexistence of depression and hypothyroidism, there was also a decrease in the level of the receptor for glucagon-like peptide 2 (GLP-2R) in all three tested models. Since this peptide, in addition to regulating food intake, has anxiolytic, neuroprotective and memory-enhancing effects [36,37], downregulation of its receptor might thus be one of the causes of anxiety-like behaviors and disruptions in spatial memory described previously in WKY animals and in the model of coexistence of depression and hypothyroidism [14]. Moreover, as with GLP-1, who's neuroprotective, improving memory and cognitive functions as well as enhancing neurogenesis and synaptic function effects are well described [37], similar effects of GLP-2 have also been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hippocampus, in addition to a decrease in the level of SNAP-25 in the model of depression and the coexistence of depression and hypothyroidism, there was also a decrease in the level of the receptor for glucagon-like peptide 2 (GLP-2R) in all three tested models. Since this peptide, in addition to regulating food intake, has anxiolytic, neuroprotective and memory-enhancing effects [36,37], downregulation of its receptor might thus be one of the causes of anxiety-like behaviors and disruptions in spatial memory described previously in WKY animals and in the model of coexistence of depression and hypothyroidism [14]. Moreover, as with GLP-1, who's neuroprotective, improving memory and cognitive functions as well as enhancing neurogenesis and synaptic function effects are well described [37], similar effects of GLP-2 have also been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Since this peptide, in addition to regulating food intake, has anxiolytic, neuroprotective and memory-enhancing effects [36,37], downregulation of its receptor might thus be one of the causes of anxiety-like behaviors and disruptions in spatial memory described previously in WKY animals and in the model of coexistence of depression and hypothyroidism [14]. Moreover, as with GLP-1, who's neuroprotective, improving memory and cognitive functions as well as enhancing neurogenesis and synaptic function effects are well described [37], similar effects of GLP-2 have also been demonstrated. For example, it has been found, that increase in GLP-2R expression enhances Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our results revealed that not only HCD but also AtDCS application influenced selected phyla of gut microbiota and the changes were associated with alternations in behavioral and metabolic parameters. Recent investigations suggest that an altered composition and diversity of gut microbiota, due to impairment in energy homeostasis, could play an important role in the development of neuropsychiatric [82] and metabolic disorders, such as obesity [83,84] Gut microbiota play a number of physiological roles involving digestion, metabolism, extraction of nutrients, synthesis of vitamins, prevention against colonization by pathogens, and immunomodulation [25,85]. The main bacterial phyla are: firmicutes (gram positive), bacteroidetes (gram negative), and actinobacteria (gram positive).…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal vagal afferents respond to a variety of chemical stimuli from gastrointestinal tract and gut microbiota can alter vagus nerve signaling by influencing the releasing of these factors from gastrointestinal cells or producing neurotransmitters such as serotonin which is involved in appetite control [95]. tDCS was shown to modulate cravings for food by influencing some brain neurotransmitters releasing [82]. We have recently demonstrated [50] that both serotonin and dopamine are involved in tDCS-induced feed restriction in obese rodents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their metabolic effect, GLP-1 RAs have also shown relevant effects in mental health. In particular, an increasing amount of research focuses on GLP-1 RAs e cacy in reducing anxiety and depressive symptoms, highlighting an important connection between metabolic regulations and psychopathological mechanisms [20][21][22][23][24]. In fact, recent studies point out that disturbed homeostasis between the nervous system and the immune and endocrine systems, disturbances in cerebral energy metabolism, and dysfunction of the gut-brain axis could play an important role in the pathogenesis of depression and anxiety: GLP-1RAs, through a modulatory effect on the immune, endocrine, and metabolic processes in the central nervous system, appear to act actively in ameliorating these symptoms [20,25].…”
mentioning
confidence: 99%